Sweat Based‐multiplexed Detection of NPY‐Cortisol for Disease Diagnostics and Stress Management. Issue 2 (28th May 2021) - Churcher, Nathan Kodjo Mintah; Upasham, Sayali; Rice, Paul; Greyling, Cornelia Felicia; Prasad, Shalini
Abstract: Cortisol and Neuropeptide Y(NPY) are chronobiological markers of stress. Non‐invasive tracking of these two biomolecules can provide great insight into an individual's physiological and neurological wellbeing. This work presents the development of a platform that tracks the two biomarkers in ultra‐low volumes (5 μL) of sweat using electrochemical impedance spectroscopy (EIS). The sensing platform was able to detect both molecules in their relevant physiological ranges (8.16–141.7 ng/mL and 50–200 pg/mL respectively) with good sensitivity and specificity. This platform is envisioned to aid in the monitoring of pathophysiologies of stress‐based disorders. Abstract :